2010
DOI: 10.1086/651075
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the American Thoracic Society–Infectious Diseases Society of America Guidelines for Hospital‐Acquired Pneumonia in the Intensive Care Unit

Abstract: The 2005 guidelines predict potentially drug-resistant microorganisms worse than the 1996 guidelines. Adherence to guidelines resulted in more adequate treatment and a trend to a better clinical response in group 2, but it did not influence mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 31 publications
2
36
1
4
Order By: Relevance
“…Our criteria for clinical suspicion of E-HAP are widely accepted. 12,13,16,18,24 Moreover, the retrospective calculation of the mCPIS allowed a positive confirmation of the diagnosis of pneumonia. 24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our criteria for clinical suspicion of E-HAP are widely accepted. 12,13,16,18,24 Moreover, the retrospective calculation of the mCPIS allowed a positive confirmation of the diagnosis of pneumonia. 24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,16,18,24 Moreover, the retrospective calculation of the mCPIS allowed a positive confirmation of the diagnosis of pneumonia. 24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported. [25][26][27][28][29] Our rate of 15.5% among liver recipients agrees with previously reported rates of pneumonia after LT ranging from 5% to 34%.…”
Section: Discussionmentioning
confidence: 99%
“…Our criteria for clinical suspicion of VAP are widely accepted 37 . Th e period of 4 days was chosen as the inclusion period for diagnosis of early VAP onset as outlined in the current American Th oracic Society/ Infectious Diseases Society of America guidelines 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical investigations of the bacteriological etiology of nosocomial pneumonia indicated that approximately 30-70% of cases had unknown etiology (Bahrani-Mougeot et al 2007;Chung et al 2011;Sopena et al 2014), but the most of them came from ventilator-associated pneumonia (VAP) patients and the data on hospital-acquired pneumonia (HAP) patients is relatively rare (Sopena et al 2014). The precise understanding of bacteriological etiology is important in HAP patients (American Thoracic Society and Infectious Diseases Society of America 2005) for appropriate empirical antimicrobial therapy that is crucial to decrease the mortality and complication rates and the length of hospital stay (Ferrer et al 2010;Jones 2010).…”
Section: Introductionmentioning
confidence: 99%